Models of Bounded Arithmetic Theories and Some Related Complexity Questions - Alam, Abolfazl; Moniri, Morteza (Bulletin of the Section of Logic, 2022)
In this paper, we study bounded versions of some model-theoretic notions and results. We apply these results to the context of models of bounded arithmetic theories as well as some related complexity questions. As an example, we show that if the theory \(\rm S_2 ^1(PV)\) has bounded model companion then \(\rm NP=coNP\). We also study bounded versions of some other related notions such as Stone topology.